Revisiting the Challenges Linked to Parenting and Home–School Relationships at the High School Level - Deslandes, Rollande; Barma, Sylvie (Canadian Journal of Education/Revue canadienne de l'éducation, 2016)
The article revisits data from a 2005 study on the parental involvement process. The purpose of this study was to analyze parents’ written statements regarding two processes: parenting and home–school relationships associated with school success at the high school level. The objectives are mainly to describe parents’ understanding of their role in adolescent education and schooling, to document their perception of adolescents’ and teachers’ invitations to become involved, and to identify contradictions within their relationships with adolescents and teachers. Using the Cultural-Historical Activity Theory (CHAT), we analyzed qualitative data obtained from 409 parents’ statements. Main findings indicate contradictions in the rules and division of labour poles of the activity systems. Divergent points of view were noted between parents and adolescents and between parents and school/teachers in regard to their responsibilities. The same observations were made with respect to home–school relationships. Other contradictions were also identified when the parents addressed the recurrent tensions to improve either their relationships with their adolescents or with the teachers. As a promising avenue for intervention and developmental research, the authors suggest to apply the Change Laboratory (CL) methodology to give adolescents a better voice and the ability to act as mediators in both activity systems.